DIPLOMASI E-COMMERCE DALAM MENDORONG KEGIATAN EKSPOR INDONESIA (STUDI KASUS KOTA SOLO) - Andika Drajat Murdani, Christy Damayanti & (Transformasi, 2018)
The e-commerce market trend is taking place around the world. This trend encourages international trade be more intense. This can be an opportunity for Indonesia to be able to develop its exports rate using e-commerce. Based on this background, this research aims to find out how the implementation of e-commerce diplomacy in encouraging export activities in Indonesia, by focusing case study in Solo. The city of Solo as a trade center needs to take advantage of this opportunity to increase its exports through e-commerce. This type of research is qualitative research because the concepts described are not standardized in numbers. The research method uses literature from primary and secondary data, that were then analyzed using qualitative descriptive techniques. The results found that the implementation of e-commerce diplomacy in Indonesia in order to encourage export activities was still not optimal. E-commerce diplomacy still faces many obstacles. The main obstacle is the low competitiveness of Indonesia's digital technology. In Solo, the use of e-commerce diplomacy has begun to be used, even though it is still not optimal. For this reason, a more appropriate strategy design is needed regarding maximazing export and to reduce export barriers related to e-commerce diplomacy.Keywords : diplomacy e-commerce, export, Indonesia, SoloPendahuluanPerkembangan ekonomi dunia banyak didorong oleh perkembangan teknologi yang pesat. Teknologi komunikasi dan informasi menciptakan global e-commerce dan online retail sebagai cara baru dalam bertransaksi. Fleksibilitas transaksi lewat e-commerce membuat berkembang dengan begitu dramatis di berbagai belahan duna. Bahkan, pasar e-commerce pun diprediksi akan terus berkembang dan belum ada tanda- tanda tren penurunan (Cohen, 2017).Pesatnya perkembangan pasar e-commerce di